First Detection of West Nile Virus by Nasopharyngeal Swab, Followed by Phylogenetic Analysis - Carlo Zuddas; Sergio Piras; Stefano Cappai; Federica Loi; Giulia Murgia; Giantonella Puggioni; Giovanni Savini; Federica Monaco; Andrea Polci; Fabrizia Valleriani; Giorgia Amatori; Valentina Curini; et al. (Pathogens)
West Nile Virus, an arthropod-borne RNA virus, may result in severe neurological disease. West Nile neuroinvasive disease is characterized by meningitis, encephalitis, and possible acute flaccid paralysis. Here, we report a case of neuroinvasive WNV in a 65-year-old woman hospitalized for hyperpyrexia, chills, intense asthenia, and continuous vomiting. Within days, her clinical condition worsened with the onset of severe neurological symptoms, leading to her death within 10 days despite supportive therapies being administered. The diagnosis of West Nile disease was made through nucleic acid amplification testing (NAAT) on blood and cerebrospinal fluid. However, in the final stages of the illness, cerebrospinal fluid collection was not possible due to the patient’s critical condition, and a nasopharyngeal swab was used instead. The nasopharyngeal swab facilitated the collection of a sample, which was subsequently analyzed for the presence of the virus and allowed for sequencing, showing that it was a strain that had been circulating in Sardinia for some time and had demonstrated its pathogenicity by causing the death of a hawk in 2021. This case report highlights the rapid progression and severity of WNV infection, particularly in vulnerable individuals, and suggests the potential utility of nasopharyngeal swabs as a less invasive option for sample collection. It also underscores the potential for the zoonotic transmission of the virus from birds to humans through vectors, emphasizing the importance of monitoring and controlling WNV outbreaks, especially in regions where such circulation is observed.